Extraskeletal Osteosarcoma: Outcomes and the Role of Chemotherapy - Paludo, Jonas (Am J Clin Oncol, 2018)
OBJECTIVES: Extraskeletal osteosarcoma (EO) is a malignant neoplasm that produces osteoid, bone, and chondroid material without direct attachment to bone or periosteum. Surgical resection is the mainstay of treatment; the role of chemotherapy is not well defined. Therefore, we evaluated the impact of chemotherapy in the survival of patients with EO. METHODS: All EO patients seen at Mayo Clinic between 1990 and 2014 were assessed. Forty-three patients were included after all archived pathology slides were reviewed to confirm the diagnosis of EO. RESULTS: Out of 43 patients, 37 patients had localized disease and 6 patients had metastatic disease at diagnosis. Chemotherapy was used in 73% and 75% of patients, respectively. Chemotherapy was predominantly anthracycline based, and included platinum in 22 patients (84%). Median overall survival (OS) and progression-free survival (PFS) were 50 months (95% CI 25–99), and 21 months (95% CI 13-NR) respectively. There was a trend towards longer OS and PFS in patients who received chemotherapy. Those who received platinum-based therapy had remarkably prolonged OS (median 182 vs. 18 months; 5-year 61% vs 0% p=0.01) and PFS (median NR vs 10 months; 5-year 56% vs. 0%; p=0.005). Baseline characteristics were similar in the platinum and non-platinum group. In patients who received chemotherapy, relapse/recurrence rate was lower in the platinum-based group (41%) as opposed to the non-platinum-based group (100%; p=0.02). In the neoadjuvant setting, the overall response rate of platinum-containing regimens was 27%. CONCLUSIONS: Our results suggest a clinical benefit when platinum-based chemotherapy is incorporated in the management of patients with EO. We plan to validate this further with an expanded multi-center analysis.